Proyecto pedagógico de aula: “anímate a expresarte” como propuesta didáctica para fortalecer la expresión oral en niños de segundo grado - Figueroa Sarria, Marly Milena (Universidad Antonio Nariño, 2024)
The purpose of this classroom pedagogical project: "Encourage yourself to express yourself" is to strengthen oral expression in second grade children of the IED Gustavo Restrepo through the design and implementation of a classroom project as a teaching strategy that aims to apply pedagogical experiences that contribute to the development and strengthening of oral expression through meaningful learning. Games, listening strategies and socio-affectivity were important elements based on theorists such as Ausubel, Helena Calsamiglia & Amparo Tusón, Daniel Cassany and Rebecca Oxford, among others, who contributed in the construction of the proposal.